Methods of Synthesis of Remdesivir, Favipiravir, Hydroxychloroquine, and Chloroquine: Four Small Molecules Repurposed for Clinical Trials during the Covid-19 Pandemic - Al Bujuq, Nader (Synthesis, 2020)
The novel coronavirus (COVID-19) disease has rapidly evolved into a sweeping pandemic despite public health measures. Screening and development of new vaccines and antivirals are expensive and time consuming. However, the repositioning of available drugs is an essential and universal strategy in the development of new drugs and therefore should receive priority attention as well as international government and agency support. Significant drugs such as chloroquine, hydroxychloroquine, favipiravir and remdesivir, are currently undergoing clinical studies to test their efficacy and safety. Some promising results have been achieved thus far in the treatment of COVID-19. In this article we summarize and discuss the most common synthetic strategies to apply in the preparation of these drug molecules. It is hoped that this compendium will provide an accessible useful guide and reference source for scientists, researchers and academia in their battle against COVD-19.1 Introduction2 Synthesis of Chloroquine (CQ) and Hydroxychloroquine (HCQ)2.1 Synthesis of 4,7-Dichloroquinoline 12.2 Synthesis of 2-Amino-5-(diethylamino)pentane (Novoldiamine) 22.3 Synthesis of 5-(N-Ethyl-N-2-hydroxyethylamino)-2-pentylamine 42.4 Developed Methods for Synthesis of Chloroquine and Hydroxychloroquine2.5 Synthesis of (R)-Chloroquine, (S)-Chloroquine, (R)-Hydroxychloroquine and (S)-Hydroxychloroquine3 Synthesis of Favipiravir (Avigan)4 Synthesis of Remdesivir5 Conclusion
Keywords: COVID-19; chloroquine; favipiravir; remdesivir; hydroxychloroquine; synthesis; antiviral